2006
DOI: 10.1186/1472-6882-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of green coffee bean extract on fat accumulation and body weight gain in mice

Abstract: BackgroundAn epidemiological study conducted in Italy indicated that coffee has the greatest antioxidant capacity among the commonly consumed beverages. Green coffee bean is rich in chlorogenic acid and its related compounds. The effect of green coffee bean extract (GCBE) on fat accumulation and body weight in mice was assessed with the objective of investigating the effect of GCBE on mild obesity.MethodsMale ddy mice were fed a standard diet containing GCBE and its principal constituents, namely, caffeine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 20 publications
9
160
0
6
Order By: Relevance
“…Cheong LK showed that high fat diet (HFD) supplemented with 0.5% w/w GCE did not attenuate weight gain in obese mice after 12 weeks [22]. However the results of the Shimoda study suggested that oral administration of 0.5% and 1% GCE was effective against weight gain and visceral fat accumulation in mice were fed with a standard diet for 14 days [23].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Cheong LK showed that high fat diet (HFD) supplemented with 0.5% w/w GCE did not attenuate weight gain in obese mice after 12 weeks [22]. However the results of the Shimoda study suggested that oral administration of 0.5% and 1% GCE was effective against weight gain and visceral fat accumulation in mice were fed with a standard diet for 14 days [23].…”
Section: Resultsmentioning
confidence: 95%
“…Scientific theories expressed that natural substances found in green coffee prevent weight gain and fat accumulation by inhibiting fat absorption and increasing fat metabolism in liver [23,29]. Supplementation with coffee polyphenols can also be effective in weight loss and reduce abdominal and liver fat accumulation by inhibition of macrophages infiltration into adipose tissues [11].…”
Section: How Does Green Coffee Extract Work For Weight Loss?mentioning
confidence: 99%
“…2 found higher correlation coeffi cients for peaks 10-15, with statistical significance for peak 10 Table 7 . Several studies have reported anti-obesity activity of neochlorogenic acid, chlorogenic acid, and rutin 5,6,9,10 . The lower correlation coeffi cients for these components may negate the possibility that they were responsible for the inhibition of obesity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of the diet with rutin decreased fat accumulation and serum lipid levels in Wistar rats that were fed a high-fat diet 9 . Shimoda et al 10 demonstrated that chlorogenic acid in green coffee beans suppresses fat accumulation and liver TG elevation in ddY mice. It is possible that these phytochemicals are responsible for the anti-obesity activity of PJT.…”
mentioning
confidence: 99%
“…Green coffee extracts show a hypotensive effect on rats (Igho et al 2011), reduce visceral fat and body weight (Shimoda et al 2006;Suzuki et al 2002), and chlorogenic acid (5-caffeoylquinic acid) can prevent from neurodegenerative diseases such as ischemic stroke (Mikami and Yamazawa 2015). Coffee brew including this from roasted beans also contains chlorogenic acids and caffeine and other bioactive compounds with antioxidant capacity such as theophylline and theobromine, tocopherols, cafestol, kahweol and trigonelline as well as products of Maillard reaction (Budryn and Nebesny 2008;Jeszka-Skowron et al 2015;Perrone et al 2008).…”
Section: Introductionmentioning
confidence: 99%